Physiological and structural analysis of light-harvesting mutants of Rhodobacter sphaeroides. - Kiley, P J (1988)
Two mutants of Rhodobacter sphaeroides defective in formation of light-harvesting spectral complexes were examined in detail. Mutant RS103 lacked the B875 spectral complex despite the fact that substantial levels of the B875-alpha polypeptide (and presumably the beta polypeptide) were present. The B800-850 spectral complex was derepressed in RS103, even at high light intensities, and the growth rate was near normal at high light intensity but decreased relative to the wild type as the light intensity used for growth decreased. Mutant RS104 lacked colored carotenoids and the B800-850 spectral complex, as well as the cognate apoproteins. This strain grew normally at high light intensity and, as with RS103, the growth rate decreased as the light intensity used for growth decreased. At very low light intensities, however, RS104 would grow, whereas RS103 would not. Structural analysis of these mutants as well as others revealed that the morphology of the intracytoplasmic membrane invaginations is associated with the presence or absence of the B800-850 complex as well as of carotenoids. A low-molecular-weight intracytoplasmic membrane polypeptide, which may play a role in B800-850 complex formation, is described, as is a 62,000-dalton polypeptide whose abundance is directly related to light intensity as well as the absence of either of the light-harvesting spectral complexes. These data, obtained from studies of mutant strains and the wild type, are discussed in light of photosynthetic membrane formation and the abundance of spectral complexes per unit area of membrane. Finally, a method for the bulk preparation of the B875 complex from wild-type strain 2.4.1 is reported.